Disparities in Energy Productivity across the EU Countries - Grodzicki, Tomasz (International Journal of Energy Economics and Policy, 2024)
Energy plays a crucial role in everyday life and thus is one of the most essential inputs in all economic activities. Nowadays, the EU energy market has changed mainly due to the Russian invasion of Ukraine. The EU countries had to suddenly adapt to the new situation and secure energy supply for their citizens. But even before that, energy issues had been raised on a global scale through the United Nations’ 2030 Agenda for Sustainable Development. One of the seventeen Sustainable Development Goals (SDGs) is SDG 7: Affordable and clean energy. Therefore, this paper aims to examine energy productivity in EU countries as it should be at the heart of the ongoing debate on energy security across the EU. This study uses two sources of data: the Eurostat and OECD. The first one provides users with a composite indicator of energy productivity, which results from the division of the GDP by the gross available energy (primary production + recovered & recycled products + imports – exports + stock changes) for a given calendar year. The latter delivers an indicator of energy productivity measured in GDP per unit of total energy supply. This paper applies the β-convergence model to investigate the disparities between the EU countries in energy productivity and to see if they are widening or narrowing over time. The results show that although there are significant initial disparities, the EU countries have been converging over time; however, the speed of that process is not satisfyingly fast.